MODEL PEMBELAJARAN ENTREPRENEURSHIP BERBASIS CREATIVEPRENEURSHIP PADA PROGRAM STUDI MAGISTER MANAJEMEN - Eddy Supriyatna; Indra Widjaja; Maria Florencia; Jethro Alva; Jessica Sarkiwan (PROSIDING SERINA, 2021)
Entrepreneurs are creators, innovators, and leaders. This means that entrepreneurship is not only the study of business, economics, and management. In fact, in the 21st Century, entrepreneurship has the main focus on the study of New Venture Creation. The word "creation" is the key word. In this context, the entrepreneurship learning model in the Master of Management study program at Tarumanagara University since 2009 has been focused on creating new businesses. It aims to create innovative businesses, so that new, different, and unique business ideas with creative problem solving will be the target of learning outcomes. Business ideas are also required to be realized in real terms, even with a simple business plan, due to the consideration of limited study time. The learning model is expected to give results in accordance with the target, and has been responded positively by the students. Therefore, the entrepreneurship learning model will be formulated as an outcome finding of the entrepreneurship learning process in the management master's study program. The formulation of the conceptual and technical learning process is a state of the art and novelty of this research, so it is hoped that the formulation can be used as guidelines in the entrepreneurship learning process. The research method used is qualitative surgery with a multidisciplinary approach. The urgency of the research is to contribute to the learning process of entrepreneurship in universities, especially the study of master of management.